Teacher and Student Collaboration in Selecting Digital Learning Resources Using Google Forms: Case Study at State Vocational School 1 Tondano, Minahasa Regency, North Sulawesi - Maukar, Merry EC; Tambingon, Henny; Rotty, Viktory NJ (Abdurrauf Science and Society, 2025)
This study aims to describe and analyze: (1) The role of Google Form in facilitating teacher-student collaboration in the selection of digital learning resources; (2) The implementation of teacher-student collaboration in selecting digital learning resources using Google Form; and (3) The supporting and inhibiting factors in the implementation of such collaboration. This research employed a qualitative method with a case study approach. The research procedures included: (1) Case selection, (2) Data collection through interviews, observation, and documentation, and (3) Data analysis. Data collection techniques consisted of interviews, observations, and document analysis. The results show that Google Form plays a significant role in supporting teacher-student collaboration through several aspects, namely: collecting students' learning resource preferences, sharing and recommending resources, encouraging self-directed learning, creating a more democratic and inclusive learning environment, and fostering students' sense of ownership in the learning process. The collaboration process took place through several stages, including teacher planning, distribution of the Google Form to students, student responses, teacher analysis of the data, and the use of the results to determine appropriate learning resources. Supporting factors for this collaboration include adequate access to technology, high student participation, availability of time and resources, and ease of data processing using Google Form. Inhibiting factors include limited technology access, varying levels of digital literacy, time constraints and lack of focus, students' unpreparedness, and teachers' difficulty in processing data. In conclusion, the use of Google Form has proven effective in enhancing student participation and engagement in the learning process, provided that sufficient digital infrastructure and literacy are in place for all parties involved.